Revealing the superlative electrochemical properties of o-B2N2 monolayer in Lithium/Sodium-ion batteries. (1st June 2022) - Khossossi, Nabil; Luo, Wei; Haman, Zakaryae; Singh, Deobrat; Essaoudi, Ismail; Ainane, Abdelmajid; Ahuja, Rajeev
Abstract: Promising flexible electrochemical energy storage systems (EESSs) are currently drawing considerable attention for their tremendous prospective end-use in portable self-powered electronic devices, including roll-up displays, and "smart" garments outfitted with piezoelectric patches to harvest energy from body movement. However, the lack of suitable battery electrodes that provides a specific electrochemical performance has made further development of these technologies challenging. Two-dimensional (2D) lightweight and flexible materials with outstanding physical and chemical properties, including mechanical strengths, hydrophilic surfaces, high surface metal diffusivity, and good conductivity, have been identified as a potential prospect for battery electrodes. In this study, taking a new 2D boron nitride allotrope, namely 2D orthorhombic diboron dinitride monolayer (o-B2 N2 ) as representatives, we systematically explored several influencing factors, including electronic, mechanical, and their electrochemical properties (e.g., binding strength, ionic mobility, equilibrium voltage, and theoretical capacity). Considering potential charge-transfer polarization, we employed a charged electrode model to simulate ionic mobility and found ionic mobility has a unique dependence on the surface atomic configuration influenced by bond length, valence electron number, electrical conductivity, excellent ionic mobility, low equilibrium voltage with excellent stability, good flexibility, and extremely superior theoretical capacity, up to 8.7 times higher than that of widely commercialized graphite (3239.74 mAh g −1 Vs 372 mAh g −1 ) in case of Li-ion batteries and 2159.83 mAh g −1 in case of Na-ion batteries, indicating that the new predicted 2D o-B2 N2 monolayer possess the capability to be ideal flexible anode materials for Lithium and Sodium-ion battery. Our finding provides valuable insights for experimental explorations of flexible anode candidates based on 2D o-B2 N2 monolayer. Highlights: New 2D Orthorhombic BN allotrope is designed as anode materials for Lithium/Sodium ion batteries. The electrochemical properties of o-B2 N2 monolayer is explored through DFT, BHMC and AIMD calculations. The o-B2 N2 possesses an extremely high capacity up to 8.7 times higher of that of commercialized graphite for Li + -storage. The Li/Na-intercalation into o-B2 N2 can improve the performance of electronic conductivity. The o-B2 N2 exhibits ultra-fast energy barriers and low open circuit voltages of Li/Na ions. Graphical abstract: